Evaluation of and selection criteria for drought resistance in Chinese semiwinter rapeseed varieties at different developmental stages. Issue 5 (29th June 2015) - Huang, Qian; Zhao, Yongguo; Liu, Chunqing; Zou, Xiling; Cheng, Yong; Fu, Guiping; Xu, Jingsong; Zhang, Xuekun; Lu, Guangyuan; Snowdon, R.
Abstract The impacts of water deficit imposed at either the germination stage or the reproductive stage on biological traits of 37 semiwinter rapeseed varieties were analysed. The osmotic stress induced by 14% polyethylene glycol had a substantial impact on seed germination and caused significant reductions in plant growth and seed vigour. Relative water content was identified as a good indicator for early screening of drought resistance. At the reproductive stage, seed yield, 1000‐seed weight, height of the first branch, plant height and number of pods per plant were all markedly reduced under the exceptionally long and severe drought condition. Two of the top three resistant genotypes at the germination stage were also shown to be resistant based on the drought susceptibility index for seed yield. Phenotypic correlation and path analyses were employed to rank the relative importance of other agronomic traits with regard to seed yield. The important contributors to seed yield under drought conditions, in descending order, were as follows: 1000‐seed weight, days to maturity, number of pods per plant and plant height.